Anomeric selectivity and influenza A virus inhibition study on methoxylated analogues of Pentagalloylglucose. (30th January 2015) - Qurat-ul-ain, Shaikh; Wang, Wei; Yang, Meiting; Du, Na; Wan, Shengbiao; Zhang, Lijuan; Jiang, Tao
Graphical abstract: Highlights: Anomeric selectivity in galloylation ofd -glucose/d -mannose was explored. The synthesized compounds were tested for anti-IAV activity on MDCK cell line. The double bond in cinnamic PGG analogues contributes for anti-IAV activity. Anomeric mixtures appeared two times more active than Ribavirin. αβ-Anomeric mixture was more potent than α- or β-pure anomers. Abstract: Anomeric selectivity in galloylation ofd -glucose andd -mannose with carboxylic acid was explored under steglich conditions. Base catalyst 4-dimethylaminopyridine favored the formation of alpha-anomers, while adding an acid and carbodiimide favored the formation of beta-anomers. Steric hindrance between α, β-unsaturated acid and C-2 OH stereochemistry (adjacent carbon to anomeric) influenced anomeric selectivity for bothd -glucose andd -mannose. The influenza A virus inhibition activities of the synthesized compounds were evaluated in Madin–Darby canine kidney cell line using the cytopathic effect inhibition assay. All the synthetic methoxylated analogues showed more considerable activity against influenza A virus than their corresponding acids, which indicated the sugar core as key functionality for anti-viral activity. The activities of trimethoxy-cinnamic acid Pentagalloylglucose analogues, 3α, 3β, 4α, and4β (IC50, 109.1 μM, 134.4 μM, 119.5 μM, 111.1 μM, respectively) were better than those of trimethoxy-benzoic acid Pentagalloylglucose analogues, 1 -αβ and 2α, 2β (IC50, 209.8 μM, 132.9 μM, 161.2 μM, respectively), which suggested that the double bond in cinnamic acid Pentagalloylglucose analogues makes the major contribution for influenza A virus inhibitory activity. Notably, several anomeric mixtures showed better activities than pure alpha or beta anomer and were almost two times more effective than Ribavirin, a clinically used anti-viral drug.